PENGEMBANGAN YOU-MATHBOOK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN PADA SISWA SD ISLAM DARUL HUDA KOTA SEMARANG - Lestari, Indah Puji; Dewi, Rida Fironika Kusuma; Ulia, Nuhyal (Universitas Muhammadiyah Surakarta, 2020)
This study aims to develop mathematical teaching materials on the subject of multiplication and find out their feasibility and practicality. This research is based on the lack of students' understanding of multiplication material and the lack of references other than worksheets or textbooks used by teachers. The renewal of this teaching material is the presence of a QR code in each chapter that can connect students to videos created by researchers and uploaded on YouTube. This study uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluate). Based on the five stages, the development of You-MathBook teaching materials resulted in a percentage of eligibility from three validators of 90.9%, a practical percentage of 84.1% and effectiveness calculated with a Gain Test of 0.35 indicating an increase in student learning outcomes in the 'medium' category. Based on these results You-MathBook teaching materials are declared feasible, practical and effective to increase understanding of the concept of multiplication in fifth (V) grade students of Darul Huda Islamic Elementary School in Semarang.